2018
DOI: 10.3892/mmr.2018.8453
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of OX40/OX40L signaling in a murine model of asthma

Abstract: The aim of the present study was to explore the roles of OX40/OX40 ligand (OX40L) signaling and OX40+ T cells in ovalbumin (OVA)-induced mouse asthma model. Asthma was induced by OVA exposure and subsequent co-treatment with OX40L protein, neutralizing anti-OX40L blocking antibody, OX40+ T cells or PBS. The protein expression levels of interleukin (IL)-4, IL-6, IL-13, IL-17, tumor necrosis factor (TNF)-α and interferon (IFN)-γ in bronchoalveolar lavage fluid (BALF) were examined using murine cytokine-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…This was further supported by Farres et al, who showed that increased expression of OX40L on B cells is associated with the level of total IgE in allergic asthma patients ( 19 ). These findings are in line with murine asthma models, in which OX40L is highly expressed by a variety of cells within the lung during an induced allergic reaction ( 20 , 21 ). Although, in general, decreased serum levels were observed in AD, adults with concomitant asthma had the highest levels of serum sOX40.…”
Section: Discussionsupporting
confidence: 83%
“…This was further supported by Farres et al, who showed that increased expression of OX40L on B cells is associated with the level of total IgE in allergic asthma patients ( 19 ). These findings are in line with murine asthma models, in which OX40L is highly expressed by a variety of cells within the lung during an induced allergic reaction ( 20 , 21 ). Although, in general, decreased serum levels were observed in AD, adults with concomitant asthma had the highest levels of serum sOX40.…”
Section: Discussionsupporting
confidence: 83%
“…And OX40-mediated costimulation signals have a major part in the primary and secondary immune responses of T cells. These signals can promote the activation, proliferation, and migration of CD4+ T cells and prolong their life, as well as can accelerate the formation of germinal centers and the differentiation and maturation of cells [ 15 , 17 ]. The OX40 expression is associated with specific T cells activated by antigen.…”
Section: Introductionmentioning
confidence: 99%
“…OX40/OX40L is a pair of important positive costimulatory signal molecules in the second signal system of T cells. OX40 (CD134) and OX40L (CD252), members of the TNF receptor superfamily (TNFRSF) and TNF superfamily (TNFSF), play important roles in T cell expansion in tumors, during infectious inflammation, and in autoimmune diseases [10, 11]. OX40 is expressed in activated T cells [12], while OX40L is mainly expressed in B lymphocytes, dendritic cells, and macrophage cells [12].…”
Section: Introductionmentioning
confidence: 99%